DAWĀ AL-QULŪB MANUSCRIPT BY MUHAMMAD KHATIB LANGGIEN (TEXT EDITING AND STUDY OF CENTRAL IDEA) - Khairatunnisak; Hermansyah; Istiqomatunnisak (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
One of the 19th-century manuscripts written in Malay Arabic-Jawi that comprises the sufi knowledge is the Dawā’ul Qulūb manuscript. The primary concepts in the manuscript and the text modifications are the subjects of this study. Given that the manuscript contains multiple variant texts, the research strategy employs the philological method in conjunction with the foundational method approach. The two manuscripts used in this study, both of which were collections of the Aceh State Museum, were found after a search of the manuscripts turned up as many as four manuscript texts. The first manuscript, with inventory number 07.1430, was used as the basic manuscript, and the second, with inventory number 07.812, was used as a comparative text. Due of its higher quality and closer (older) age to the autograph text, text 07.1430 was picked. Nevertheless, moral illness and how to prevent it are the focus of this manuscript's main concept. According to the findings of this study, the Dawā’ul Qulūb manuscript, which contains Islamic teachings on sufism, contains two parts: first; corrected text with a critical edition, and second; knowing clearly and in detail the contents of the Dawā’ul Qulūb manuscript which contains Islamic teachings on the Sufism knowledge. Some of the sub-chapters contained in the manuscript include: immoral parts of body, immoral hearts, and obedient in the heart.